Mechanisms and moderators in mindfulness‐ and acceptance‐based treatments for binge eating spectrum disorders: A systematic review. (19th March 2019) - Barney, Jennifer L.; Murray, Helen B.; Manasse, Stephanie M.; Dochat, Cara; Juarascio, Adrienne S.
Abstract: Objective: Increasing evidence suggests that mindfulness‐ and acceptance‐based psychotherapies (MABTs) for bulimia nervosa (BN) and binge eating disorder (BED) may be efficacious; however, little is known about their active treatment components or for whom they may be most effective. Methods: We systematically identified clinical trials testing MABTs for BN or BED through PsychINFO and Google Scholar. Publications were categorized according to analyses of mechanisms of action and moderators of treatment outcome. Results: Thirty‐nine publications met inclusion criteria. Twenty‐seven included analyses of therapeutic mechanisms, and five examined moderators of treatment outcome. Changes were largely consistent with hypothesized mechanisms of MABTs, but substandard mediation analyses, inconsistent measurement tools, and infrequent use of mid‐treatment assessment points limited our ability to make strong inferences. Discussion: Analyses of mechanisms of action and moderators of outcome in MABTs for BN and BED appear promising, but the use of more sophisticated statistical analyses and adequate replication is necessary.